Impact and challenges of e-government implementation in Nigeria: a systematic literature review - Ayesha, Adeleye Dupe; Ahlan, Abd. Rahman; Muhamad Ibrahim, Najhan; Ahmed, Mahfooz (IIUM Press, 2025)
E-government, the use of information and communication technologies (ICT) to deliver government services electronically, offers numerous benefits, such as streamlined processes, reduced paperwork, and enhanced transparency. Nigeria’s e-government journey, initiated in the early 2000s, aims to modernize public administration. However, infrastructure deficits, corruption, and limited digital literacy impede its full potential. This systematic review explores the impacts of e-government services on citizens, businesses, and government agencies in Nigeria and reveals the challenges associated with e-government implementation based on existing literature. Following the PRISMA guidelines, a comprehensive literature search was conducted in SCOPUS and Dimensions databases, focusing on peer-reviewed articles (2000-2024). The Mixed Methods Appraisal Tool (MMAT) was used to assess the methodological quality, resulting in 26 included studies. Findings reveal significant enhancements in government service delivery, transparency, and public participation. 85% of reviewed studies reported efficiency improvements, with systems like IPPIS reducing financial leakages and streamlining HR management. Increased citizen engagement through digital platforms was highlighted by 70% of studies, fostering trust. Critically, over 90% of studies identified poor ICT infrastructure and unreliable power supply as major barriers, while 75% emphasized the negative impact of corruption and low digital literacy. Qualitative synthesis revealed that lack of political will and inconsistent policy implementation were critical obstacles, with only 20% of studies reporting sustained government commitment. While e-government holds transformative potential for Nigeria, addressing these challenges demands targeted interventions, including infrastructure development, digital literacy programs, and stronger policy frameworks. Political will and multi-stakeholder collaboration are crucial for realizing e-government’s full potential